STRUKTUR RUANG PERMUKIMAN SUKU ATONI BERBASI BUDAYA, STUDI KASUS: KAMPUNG ADAT TAMKESI, KABUPATEN TIMOR TENGAH UTARA - Tallo, Amandus Jong (Unika Soegijapranata Semarang, 2013)
ABSTRACT Since the olden days the culture of settling was realized as one of the important heritages handed down from generation to generation. In a society that firmly upheld their culture, such as Balinese, the settlement structure was determined by the cosmic system. It was concretized by the existence of the mountain as the orientation of a sacred space and the ocean as the orientation profane space. In Yogyakarla the settlement structure was determined by a persons life cycle that was described by South Ocean to Mount Merapi. One of the philosophies in determining a spatial structure was based on kinship system and sex. Atoni people arranged their settlement space based on kinship in which the spatial organization of was formed on the basis of gender or sexual difference. Atonis settling culture could be recognized by spatial symbolism that was strongly associated with sexual dichotomy. Each cardinal direction that was associated with only one sex was not always consistent because the head of the community was called